Genome-wide analysis and characterization of Dendrocalamus farinosus SUT gene family reveal DfSUT4 involvement in sucrose transportation in plants - Deng, Bin; Gu, Xiaoyan; Chen, Sen; Zhang, Meng; Hao, Suwei; Wei, Lixian; Cao, Ying; Hu, Shanglian (Frontiers in Plant Science, 2023)
Sucrose is the main transported form of photosynthetic products. Sucrose transporter (SUT) participates in the translocation of sucrose from source to sink, which is important for the growth and development of plants. Dendrocalamus farinosus is an important economic crop in southwestern China because of its high growth rate, high fiber content, and dual usage for food and timber, but the mechanism of sucrose transportation in D. farinosus is unclear. In this study, a total of 12 SUT transporter genes were determined in D. farinosus by whole-genome identification. DfSUT2, DfSUT7, and DfSUT11 were homologs of rice OsSUT2, while DfSUT4 was a homolog of OsSUT4, and these four DfSUT genes were expressed in the leaf, internode, node, and bamboo shoots of D. farinosus. In addition, DfSUT family genes were involved in photosynthetic product distribution, ABA/MeJA responses, and drought resistance, especially DfSUT4. The function of DfSUT4 was then verified in Nicotiana tabacum. DfSUT4 was localized mainly in the leaf mesophyll and stem phloem of pDfSUT4::GUS transgenic plant. The overexpression of DfSUT4 gene in transgenic plant showed increases of photosynthetic rate, above-ground biomass, thousand grain weight, and cellulose content. Our findings altogether indicate that DfSUT4 can be a candidate gene that can be involved in phloem sucrose transportation from the source leaves to the sink organs, phytohormone responses, abiotic stress, and fiber formation in plants, which is very important in the genetic improvement of D. farinosus and other crops.